Supervision Activities of the Principal in Achieve Effective Online Learning with a Parental Supervision Approach - Mokhamad Yaurizqika Hadi; Nur Ittihadatul ummah (The Faculty of Education and Teaching Training, 2022)
From 2020 until 2022, Indonesia's Covid 19 pandemic became an epidemic. The government issued a policy in this case, educational institutions to eliminate face-to-face learning activities and learning with online learning. In its implementation, of course, there are many obstacles, especially since most students find it difficult to follow the bold learning process. This article analyzes the problems that occur in bold learning and describe effective bold learning with the involvement of the principal as a school supervisor to maximize school resources, in this case, parents with a Parental Supervision approach. This study uses a comparative qualitative research method with a qualitative approach. The results of this study found that in the implementation of online learning, there were at least three problems, namely, the lack of supporting facilities. Second, mastery of technology is not optimal. Third, the role of the principal as a school supervisor is not maximized in the process of supervising bold learning. Therefore, the role of the principal as a school supervisor is essential who can encourage parental involvement in the Parental Supervision approach to realize effective bold learning. Dari tahun 2020 hingga 2022, pandemi Covid 19 di Indonesia menjadi epidemi. Pemerintah mengeluarkan kebijakan dalam hal ini lembaga pendidikan untuk meniadakan kegiatan pembelajaran tatap muka dan pembelajaran dengan pembelajaran online. Dalam pelaksanaannya tentunya banyak mengalami kendala terutama karena sebagian besar siswa merasa kesulitan untuk mengikuti proses pembelajaran yang berani. Artikel ini menganalisis permasalahan yang terjadi dalam pembelajaran berani dan mendeskripsikan pembelajaran berani yang efektif dengan keterlibatan kepala sekolah sebagai pengawas sekolah untuk memaksimalkan sumber daya sekolah, dalam hal ini orang tua dengan pendekatan Pengawasan Orang Tua. Penelitian ini menggunakan metode penelitian kualitatif komparatif dengan pendekatan kualitatif. Hasil penelitian ini menemukan bahwa dalam pelaksanaan pembelajaran online setidaknya terdapat tiga permasalahan yaitu kurangnya fasilitas penunjang. Kedua, penguasaan teknologi yang belum optimal. Ketiga, peran kepala sekolah sebagai pengawas sekolah belum maksimal dalam proses pengawasan pembelajaran yang berani. Oleh karena itu, peran kepala sekolah sebagai pengawas sekolah sangat penting yang dapat mendorong keterlibatan orang tua dalam pendekatan Pengawasan Orang Tua untuk mewujudkan pembelajaran berani yang efektif.